Calculation of the pKa of 1-(o-Hydroxyphenyl) Imidazole Carboxylic Esters Using the ab initio, DFT and PCM— UAHF models - REZAEI-SAMETI, MAHDI (Asian Journal of Chemistry, 2010)
The acidity of different classes of imidazole esters in aqueous solution has been calculated. The calculation are carried out at SCF and B3LYP level with inclusion of entropic and thermo chemical correction to yield free energies of dissociation, using the basis sets 6-31G** and the recently parameterized continuum-solvation method PCMUAHF for the solvation contribution. The model furnishes pKa values in relatively in good agreement with experimental data. Scaling different parts of solvation energies provides a significant improvement in results and signifies the importance of balance of individual contributions from electrostatic, cavity, dispersion and repulsion interactions.